Understanding the efficient electrocatalytic activities of MoSe2–Cu2S nanoheterostructures. Issue 15 (7th April 2021) - Hassan, Md. Samim; Basera, Pooja; Gahlawat, Soniya; Ingole, Pravin P.; Bhattacharya, Saswata; Sapra, Sameer
Abstract : The epitaxial growth of Cu2 S NCs over the inert basal planes of MoSe2 NSs increases the number of active sites for OER. The built-in electric field at interfaces greatly favors the OER and HER activities via decreasing the energy barriers. Abstract : The electrocatalytic water splitting activity of layered transition metal dichalcogenides (TMDs) is limited by inert basal planes and slower reaction kinetics. Here, we demonstrate the use of MoSe2 –Cu2 S nanoheterostructures (NHSs) as an efficient electrocatalyst for water splitting. The interfacial engineering of the basal planes of MoSe2 nanosheets (NSs) with Cu2 S nanocrystals (NCs) increases the number of active sites for oxygen evolution reaction (OER), owing to the decoration of inert basal planes of MoSe2 NSs with an OER active material i.e . Cu2 S NCs. Density functional theory calculations revealed a favorable type-II band alignment, and built-in electric field at heterointerfaces, significantly decreasing the energy barrier for interfacial charge transfer. As a consequence of the simultaneous increase of number of active sites and modulation of the electronic structure, the MoSe2 –Cu2 S NHSs exhibit higher OER activity with an overpotential of 264 mV at 10 mA cm −2 current density. The built-in electric field phenomenon also greatly promotes hydrogen evolution reaction (HER) activity of MoSe2 –Cu2 S NHSs in alkaline medium on account of the decreased kinetic energy barrier. This study sheds light on the importance of designing NHS-derived systems to tune the electrocatalytic properties for water splitting.